Cholesterol modulates open probability and desensitization of NMDA receptors - Korinek, Miloslav; Vyklicky, Vojtech; Borovska, Jirina; Lichnerova, Katarina; Kaniakova, Martina; Krausova, Barbora; Krusek, Jan; Balik, Ales; Smejkalova, Tereza; Horak, Martin; Vyklicky, Ladislav (The Journal of physiology, 2015)
NMDA receptors (NMDARs) are glutamate-gated ion channels that mediate excitatory neurotransmission in the CNS. Although these receptors are in direct contact with plasma membrane, lipid-NMDAR interactions are little understood. In the present study, we aimed at characterizing the effect of cholesterol on the ionotropic glutamate receptors. Whole-cell current responses induced by fast application of NMDA in cultured rat cerebellar granule cells (CGCs) were almost abolished (reduced to 3%) and the relative degree of receptor desensitization was increased (by seven-fold) after acute cholesterol depletion by methyl-β-cyclodextrin. Both of these effects were fully reversible by cholesterol repletion. By contrast, the responses mediated by AMPA/kainate receptors were not affected by cholesterol depletion. Similar results were obtained in CGCs after chronic inhibition of cholesterol biosynthesis by simvastatin and acute enzymatic cholesterol degradation to 4-cholesten-3-one by cholesterol oxidase. Fluorescence anisotropy measurements showed that membrane fluidity increased after methyl-β-cyclodextrin pretreatment. However, no change in fluidity was observed after cholesterol enzymatic degradation, suggesting that the effect of cholesterol on NMDARs is not mediated by changes in membrane fluidity. Our data show that diminution of NMDAR responses by cholesterol depletion is the result of a reduction of the open probability, whereas the increase in receptor desensitization is the result of an increase in the rate constant of entry into the desensitized state. Surface NMDAR population, agonist affinity, single-channel conductance and open time were not altered in cholesterol-depleted CGCs. The results of our experiments show that cholesterol is a strong endogenous modulator of NMDARs.
Keywords: fluidita membrány; anticholesteremika; beta-Cyclodextrins; Cholesterol; Cerebellum; cholesterol; Electrophysiological Phenomena; Simvastatin; nervové vedení; membránové lipidy; Female; Patch-Clamp Techniques; Receptors, N-Methyl-D-Aspartate; krysa rodu Rattus; zvířata; Anticholesteremic Agents; Cells, Cultured; metoda terčíkového zámku; elektrofyziologické jevy; potkani Wistar; Synaptic Transmission; receptory N-methyl-D-aspartátu; cholesterol oxidasa; beta-cyklodextriny; Neural Conduction; ženské pohlaví; nervový přenos; Rats, Wistar; Male; kultivované buňky; Membrane Fluidity; mozeček; Rats; Cholesterol Oxidase; Animals; mužské pohlaví; Membrane Lipids; simvastatin